A randomized trial to investigate needle redirections/re-insertions using a handheld ultrasound device versus traditional palpation for spinal anesthesia in obese women undergoing cesarean delivery. (February 2022) - Weiniger, C.F.; Carvalho, B.; Ronel, I.; Greenberger, C.; Aptekman, B.; Almog, O.; Kagan, G.; Shalev, S.
Highlights: Automated handheld ultrasound (H-US) identifies neuraxial block insertion point. H-US vs. palpation was compared in obese women undergoing spinal anesthesia. Primary outcome was a composite of number of redirections and re-insertions. There was no difference in primary outcome between H-US and palpation groups. Abstract: Background: Ultrasound may be useful to identify the spinal anesthesia insertion point, particularly when landmarks are not palpable. We tested the hypothesis that the number of needle redirections/re-insertions is lower when using a handheld ultrasound device compared with palpation in obese women undergoing spinal anesthesia for cesarean delivery. Methods: Study recruits were obese (body mass index (BMI) >30 kg/m 2 ) women with impalpable bony landmarks who were undergoing spinal anesthesia for elective cesarean delivery. Women were randomized to ultrasound or palpation. The primary study outcome was a composite between-group comparison of total number of needle redirections (any withdrawal and re-advancement of the needle and/or introducer within the intervertebral space) or re-insertions (any new skin puncture in the same or different intervertebral space) per patient. Secondary outcomes included insertion site identification time and patient verbal numerical pain score (0–10) for comfort during surgical skin incision. Results: Forty women completed the study. The mean BMI (standard deviation) for the ultrasound group was 39.8 (5.5) kg/m 2 and for the palpation group 37.3 (5.2) kg/m 2 . There was no difference in the composite primary outcome (median (interquartile range) [range]) between the ultrasound group (4 (2–13) [2–22]) and the palpation group (6 (4–10) [1–17]) ( P =0.22), with the 95% confidence interval of the difference 2 (−1.7 to 5.7). There were no differences in the secondary outcomes. Conclusions: Handheld ultrasound did not demonstrate any advantages over traditional palpation techniques for spinal anesthesia in an obese population undergoing cesarean delivery, although the study was underpowered to show a difference.